Impaired Endosome Maturation Mediates Tubular Proteinuria in Dent Disease Cell Culture and Mouse Models. Issue 4 (9th February 2023) - Shipman, Katherine E.; Baty, Catherine J.; Long, Kimberly R.; Rbaibi, Youssef; Cowan, Isabella A.; Gerges, Mona; Marciszyn, Allison L.; Kashlan, Ossama B.; Tan, Roderick J.; Edwards, Aurélie; Weisz, Ora A.
Abstract : Abstract : Significance Statement: Loss of function of the 2Cl − /H + antiporter ClC-5 in Dent disease causes an unknown impairment in endocytic traffic, leading to tubular proteinuria. The authors integrated data from biochemical and quantitative imaging studies in proximal tubule cells into a mathematical model to determine that loss of ClC-5 impairs endosome acidification and delays early endosome maturation in proximal tubule cells, resulting in reduced megalin recycling, surface expression, and half-life. Studies in a Dent mouse model also revealed subsegment-specific differences in the effects of ClC-5 knockout on proximal tubule subsegments. The approach provides a template to dissect the effects of mutations or perturbations that alter tubular recovery of filtered proteins from the level of individual cells to the entire proximal tubule axis. Background: Loss of function of the 2Cl − /H + antiporter ClC-5 in Dent disease impairs the uptake of filtered proteins by the kidney proximal tubule, resulting in tubular proteinuria. Reduced posttranslational stability of megalin and cubilin, the receptors that bind to and recover filtered proteins, is believed to underlie the tubular defect. How loss of ClC-5 leads to reduced receptor expression remains unknown. Methods: We used biochemical and quantitative imaging data to adapt a mathematical model of megalin traffic in ClC-5 knockout and control cells. Studies in ClC-5 knockout mice were performed to describe the effect of ClC-5 knockout on megalin traffic in the S1 segment and along the proximal tubule axis. Results: The model predicts that ClC-5 knockout cells have reduced rates of exit from early endosomes, resulting in decreased megalin recycling, surface expression, and half-life. Early endosomes had lower [Cl − ] and higher pH. We observed more profound effects in ClC-5 knockout cells expressing the pathogenic ClC-5E211G mutant. Alterations in the cellular distribution of megalin in ClC-5 knockout mice were consistent with delayed endosome maturation and reduced recycling. Greater reductions in megalin expression were observed in the proximal tubule S2 cells compared with S1, with consequences to the profile of protein retrieval along the proximal tubule axis. Conclusions: Delayed early endosome maturation due to impaired acidification and reduced [Cl − ] accumulation is the primary mediator of reduced proximal tubule receptor expression and tubular proteinuria in Dent disease. Rapid endosome maturation in proximal tubule cells is critical for the efficient recovery of filtered proteins.